Pengaruh Aktivitas Pasar dan Reputasi Underwriter terhadap Excess Returns Saham IPO di Bursa Efek Indonesia - Utamaningsih, Arni (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2014)
This study provides comprehensive analysis of an IPO (Initial Public Offering) underwriting process. It considers the set of actions that an underwriter undertakes as an integrated process, explicitly recognizing the interdependencies among pre market, issue-date, and aftermarket underwriter activities. It can be drawn only if these relationships are fully rather than partially considered. This analysis clarifies the relationships between the various underwriter activities and the returns that investors earn during different periods after the offerings. It also shows that an underwriter reputation has implications for both underwriter activities during the underwriting process and investor returns.Underwriter reputation is a positive but weakly determinant of pre market underwriter activities, unrelated to aftermarket price stabilization activities, and unrelated to investor returns. Pre market underwriter activities are a significant determinant of initial returns but unrelated to aftermarket activities and short-run returns. Initial returns are significantly related to aftermarket underwriter activities and longer-run returns. The results suggest for a simultaneous consideration of underwriter reputation and market activities, and for which path analysis can be drawn about the IPO as a set of process and investor returns.